Prevalence and factors associated with social anxiety disorder among secondary school adolescents in Kathmandu metropolitan, Nepal. - Tamang,Dichhen (2020)
ABSTRACT: Introduction: Social anxiety is intense anxiety or fear of being judged, negatively evaluated, or rejected in a social or performance situation. Social Anxiety Disorder is the third largest mental health care problem in the world today. Social anxiety often develops in childhood or early adolescence, which eventually grows up to adulthood mostly without being diagnosed. Significant impacts of SAD can be seen in adolescent's schooling, peer relationship, self-esteem and their family environment. This study assessed the prevalence and factors associated with social anxiety disorders in secondary school adolescents. Methodology: School based survey method and cross-sectional analytical study design were performed among secondary school adolescents of Kathmandu Metropolitan. The multi-stage random sampling was done to obtain a sample. A self-administered questionnaire was used as data collection tool. LSAS-CA was used as tool for determining SAD. Reliability and validity were maintained by applying different strategies. Data entry and analysis were by using software Epi Data and SPSS software as per the data analysis plan. Research ethics was maintained. Results: The prevalence of SAD was 39.7% which was higher in females (47.6%) than male (37%). The study found that 33.3% of the participants were in the pre syndromal category. A strong association (p < .001) was seen between self-perception related variables and SAD. Relationship with family and friends and strictness of parents were found to be associated with SAD. Similarly, a significant relationship (p < .001) was found between social experience related variables and SAD which included: the experience of being in a traumatic situation, discrimination and being bullied. Conclusion: There was a high prevalence of SAD among adolescents. One third of the participants are in the pre syndromal category clearly stating that the diagnosed cases only represented the tip of the iceberg. Health education and school-based youthfriendly mental health service might be very helpful. Keywords: Social anxiety disorder, Secondary school adolescents, Factors associated with SAD, Self-perception, Peer victimization.